From SARS to Avian Influenza: The Role of International Factors in China's Approach to Infectious Disease Control - Fiona C. Goldizen (Ubiquity Press, 2016)
Background: Over the past decades global environmental change, globalization, urbanization, and the rise in movement of people have increased the risk for pandemic disease outbreaks. As environmental exposures do not respect state borders, a globalist concept of global healthresponse has developed, which requires transparency and cooperation for coordinated responses to disease outbreaks. Countries that avoid cooperation on health issues for social or political reasons can endanger the global community. Objectives: The aim of this study was to examine the rapid change in China's infectious disease policy between 2000 and 2013, from actively rejecting the assistance of international health experts during the HIV/AIDS and severe acute respiratory syndrome crises to following best-practice disease response policies and cooperating with international health actors during the 2013 avian influenza outbreak. Methods: Using international relations theory, I examined whether international political factors had a major influence on this change. Using the case studies of international reputation, socialization with international organizations, and the securitization of infectious disease, this study examined the influence of international and domestic pressures on Chinese infectious disease policy. Findings: Although international relations theory, especially theories popular in global health diplomacy literature, provide valuable insight into the role of international factors and foreign policy interests in China's changing approach to infectious disease control, it cannot provide viable explanations without considering the domestic interests of the Chinese government. Conclusion: Analysis of state responses to infectious disease using international relations theories must consider domestic political factors.